2021
DOI: 10.1002/asi.24612
|View full text |Cite
|
Sign up to set email alerts
|

Pandemics are catalysts of scientific novelty: Evidence from COVID‐19

Abstract: Scientific novelty drives the efforts to invent new vaccines and solutions during the pandemic. First-time collaboration and international collaboration are two pivotal channels to expand teams' search activities for a broader scope of resources required to address the global challenge, which might facilitate the generation of novel ideas. Our analysis of 98,981 coronavirus papers suggests that scientific novelty measured by the BioBERT model that is pretrained on 29 million PubMed articles, and first-time col… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 79 publications
(121 reference statements)
0
15
0
2
Order By: Relevance
“…When excluding international collaborations and productive features, we found that the performance decreased (Recall = 0.63, Precision = 0.37, AUC = 0.61), which means the two author-related features are important. Although a research investigated Scopus data of 2005 found that international collaboration tends to produce conventional research (Wagner et al, 2019 ), a recently study focused on COVID-19 field reached the opposite conclusion (Liu et al, 2021 ). Our study of materials science supported, to some extent, the later opinion, for the reason that this filed is labor intensive and device induced.…”
Section: Resultsmentioning
confidence: 99%
“…When excluding international collaborations and productive features, we found that the performance decreased (Recall = 0.63, Precision = 0.37, AUC = 0.61), which means the two author-related features are important. Although a research investigated Scopus data of 2005 found that international collaboration tends to produce conventional research (Wagner et al, 2019 ), a recently study focused on COVID-19 field reached the opposite conclusion (Liu et al, 2021 ). Our study of materials science supported, to some extent, the later opinion, for the reason that this filed is labor intensive and device induced.…”
Section: Resultsmentioning
confidence: 99%
“…This approach has been leveraged in previous work on the analysis of patent novelty, where document embedding models have been used to generate feature vector representations for patents, allowing the cosine similarity between them to be calculated [20]. There are also domain specific models that can be used for document embeddings, such as BioBERT, which as has similarly been used to assess the relative novelty of PubMed Articles by generating document feature vectors [37].…”
Section: Related Literature 21 Novelty Metricsmentioning
confidence: 99%
“…Accordingly, researchers are likely to prefer "known collaborators" (Fry et al, 2020), which could disadvantage those outside the network. Nevertheless, the pandemic motivated researchers to collaborate with those with whom they had not previously worked, with such first-time international collaboration positively associated with the novelty of research (Liu et al, 2021).…”
Section: Equitable Opportunities For Virtual Academic Mobility In Asiamentioning
confidence: 99%